Individual psychological distance: a leadership task to assess and cope with invisible change. Issue 3 (2nd March 2021) - Abbas, Ansar; Ekowati, Dian; Suhariadi, Fendy
Abstract : Purpose: The current research review aims to provide a conceptual framework for future research on individual psychological distance in leadership tasks. Design/methodology/approach: Through literature review, the authors developed an intended research framework. Findings: The need of intended framework from theoretical perspective, meta-analysis and situational analysis is presented in this paper. The discussion on a present study about the various aspects of individual perspective, strategic leadership and its link with organizational outcomes are hypothetically aligned in the framework. Originality/value: Strategic change management is the process of managing change in an organization. Change is critical to measure existing structures in the thoughtful way. Mapping individual behavior change is a difficult task, and organizational goals, objectives and missions are an important element of the learning process. Through this framework, the authors attempt to reach the model.